Crowdfunding independent and freelance journalism: Negotiating journalistic norms of autonomy and objectivity. (February 2015) - Hunter, Andrea
In recent years, news organizations have been struggling to find viable business models, with many media outlets either closing or facing budget cuts, resulting in fewer journalists working with fewer resources. One solution that has been gaining momentum is the practice of crowdfunding. This move has been heralded as one that puts audiences in a position of power, in that they have a say in what journalists pursue, but how does the role of the professional journalist change when giving up some control of the news process? This article argues that journalists who crowdfund strongly believe in the journalistic norm of autonomy, but at the same time feel a great deal of responsibility towards their funders, which is potentially a point of conflict. They also challenge the journalistic norm of objectivity, often using crowdfunding as an avenue to create journalism with a 'point of view', or advocacy journalism.